The microbiomic signature of hemorrhoids and comparison with associated microbiomes - Wang, Yuquan; Su, Wenya; Liu, Zhiqiang; Wang, Yihua; Li, Ling; Xu, Hai; Wang, Mingyu; Shen, Wenlong (Frontiers in microbiology, 2024)
Hemorrhoids are a common ailment that can cause significant disruptions to one’s daily life. While some researchers have speculated about a potential link between hemorrhoid development and gut microbes, there is currently insufficient evidence to support this claim. In this study, we collected samples from 60 hemorrhoid patients and analyzed the composition and characteristics of microbiomes in hemorrhoids. PCoA results revealed distinct differences between the microbiomes of hemorrhoids, skin-originated microbiomes, and gut microbes, highlighting the complex nature of hemorrhoidal microbiomes. The distribution characteristics of Staphylococcus suggest that the skin microbiome influences the microbiome of hemorrhoids. Additionally, we observed higher levels of Prevotella in two cases of thrombosed hemorrhoids compared to non-thrombosed hemorrhoids. This finding suggests that Prevotella may play a crucial role in the development of thrombosed hemorrhoids.